2020
DOI: 10.1017/cls.2019.21
|View full text |Cite
|
Sign up to set email alerts
|

Play-by-Play Justice: Tweeting Criminal Trials in the Digital Age

Abstract: Journalists routinely live-tweet high-profile criminal trials, a practice that raises questions about access to justice and the principle of open court. Does social media open up the justice system? There is a normative debate in the literature about the use of Twitter and social media in the courtroom. This paper takes on this debate by exploring the relationship between digital technologies and criminal justice. Through a systematic examination of journalists’ tweets during two key trials (Ghomeshi and Saret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The boom in live blogging legal trials has led to a concomitant academic interest which thus far has lifted how the use of social media and twitter impact on open justice with a focus on the transparency, accountability and openness of legal documents (such as the preliminary investigation or judgement) and processes (from law-making, to policework, to legal trials) (Hall-Coates, 2015; Janoski-Haehlen, 2011; Johnston, 2018; Lambert, 2011; Rodrick, 2014; Small & Puddister, 2020; Winnick, 2014); how audiences interact with such reports (Coulling & Johnston, 2018; Marty et al, 2016) and; how live blogs are written (Knight, 2017). A more explicit focus on the legal professionals being depicted – how they perceive the extra scrutiny that live blogging entails – is missing, as is insight into how live blogs are related to and used by legal professionals.…”
Section: Previous Research On Live Blogs and Legal Trialsmentioning
confidence: 99%
“…The boom in live blogging legal trials has led to a concomitant academic interest which thus far has lifted how the use of social media and twitter impact on open justice with a focus on the transparency, accountability and openness of legal documents (such as the preliminary investigation or judgement) and processes (from law-making, to policework, to legal trials) (Hall-Coates, 2015; Janoski-Haehlen, 2011; Johnston, 2018; Lambert, 2011; Rodrick, 2014; Small & Puddister, 2020; Winnick, 2014); how audiences interact with such reports (Coulling & Johnston, 2018; Marty et al, 2016) and; how live blogs are written (Knight, 2017). A more explicit focus on the legal professionals being depicted – how they perceive the extra scrutiny that live blogging entails – is missing, as is insight into how live blogs are related to and used by legal professionals.…”
Section: Previous Research On Live Blogs and Legal Trialsmentioning
confidence: 99%
“…Research on carceral institutions in Canada by settler political scientists is still emerging and does not centre on relationality and abolition. The themes of this literature focus on the judiciary (Riddell and Baker, 2018; Small and Puddister, 2020); 10 political ideology (Kelly and Puddister, 2017; Gordon, 2021); 11 criminalization (Hindmarch et al, 2018; Hindmarch and Orsini, 2021; Kilty and Orsini, 2019a, 2019b; Kilty et al, 2017; Johnson and Porth, 2023); 12 and colonial violence, genocide and residential schools (MacDonald, 2020; MacDonald and Hudson, 2012; Murray, 2017). 13 One political scientist offers work using the specific focus and language of the Canadian carceral state: Robert Nichols.…”
Section: Indigenous and Settler Literature In Canada And Beyondmentioning
confidence: 99%
“…As social media also allows individuals to share news stories, this study found that between 10 and 15% of the sample shared information on one of the cases (Rose & Fox, 2014). Social media also allows the opportunity for journalists to share information about criminal proceedings such as court cases (Small & Puddister, 2020). Journalists providing the public with updates allow a glimpse into what is happening in the court but it does not facilitate any engagement between this branch of the criminal justice system and the public (Small & Puddister, 2020).…”
Section: Social Media In Criminal Justicementioning
confidence: 99%
“…Social media also allows the opportunity for journalists to share information about criminal proceedings such as court cases (Small & Puddister, 2020). Journalists providing the public with updates allow a glimpse into what is happening in the court but it does not facilitate any engagement between this branch of the criminal justice system and the public (Small & Puddister, 2020). The court system is one aspect of the entire criminal justice system that interacts with social media usage.…”
Section: Social Media In Criminal Justicementioning
confidence: 99%